Sociodemographic factors influencing knowledge, attitude, and practices regarding the prevention of common cancers among adults in urban slum, Kolkata - Paramita Sarkar; Arnab Sarkar; Rivu Basu (Wolters Kluwer Medknow Publications, 2022)
Context: Cancer is a serious global public health problem. Public awareness plays a big role in the prevention of cancer. Aims: This study aims to evaluate influence of sociodemographic characteristics and related factors on knowledge, attitude, and practice (KAP) regarding the prevention of common cancers. Settings and Design: This community-based observational, cross-sectional study was conducted in the slum area of urban field practice area of a tertiary care hospital, Kolkata. Materials and Methods: The survey was conducted with a sample of 415 using a semistructured questionnaire related to KAP regarding the prevention of cancers. Mann-Whitney U-test and Kruskal-Wallis test were conducted to determine group differences for sociodemographic variables. Linear correlational analysis was performed to identify associated factors and measure the strength and direction of relationships Results: Median scores for knowledge, attitude, and practice differed by sociodemographic characteristics. Positive correlations were observed between knowledge-attitude (r = 0.395, P < 0.01), attitude-practice (r = 0.391, P < 0.01), and knowledge-practice (r = 0.460, P < 0.01). Age, gender, educational status, and socioeconomic class were significantly associated with KAP score of participants. Conclusions: Knowledge about primary preventive measure was found to be less. The study found varying degrees of positive correlation between KAP. Knowledge and level of education had positive associations with attitude and adherence to preventive measures. The findings suggest a need for targeted community awareness interventions for the elderly populations, among men and those with no school education. The positive linear correlations reaffirm that better knowledge can lead to positive attitude and subsequently in good practices. Extensive health educational campaigns should be provided to the general population.